MISUSING PREVENTIVE DETENTION IN SECURITY LEGISLATIONS: A HISTORICAL ANALYSIS FROM THE LENS OF PERSONAL LIBERTY - Sardar, Lohit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Preventive Detention is an extraordinary instrument used during times of crisis to prevent the commission of criminogenic behaviour by curtailing individual liberty on the apprehension of a criminal act, in the interests of national security. However, within Indian law, this extraordinary power holds a peculiar position in the sense that it is applicable during peacetime as well, an anomaly from the juristic position that it occupies in other jurisdictions. The historical roots of this power are traceable from the colonial era, wherein it was used as a means to silence dissent against the colonial State, yet, even after independence, it was given constitutional recognition and included and incorporated into the constitutional mechanism within Article 22. This is perhaps attributable to the exceptional circumstances surrounding the birth of this nascent nation, yet, over the past seven decades, it has been used as a means of silencing dissent and curtailing the voices of opposition, primarily due to its loose, imprecise, and vague connotation, as well as the blanket power that has been constitutionally granted on the State to exercise preventive detention. Curiously, although the judiciary has historically been an avowed protector of individual liberty and freedom, petitions challenging the validity of preventive detention legislations have often fallen on deaf ears, with the judiciary repeatedly valuing the principles of national security that these legislations envisage to protect over the individual rights of liberty and freedom. Thus, over the past seven decades, the misuse and abuse of preventive detention have become a dark spot in Indian legislative and judicial history. Against this backdrop, this paper is interested in examining the historical development and application of preventive detention laws in India, starting from the colonial period and expanding the discussion to the present, to understand the reasoning for its implementation during the British era, its subsequent inclusion within the constitutional framework, its use and misuse over the decades and the judicial opinion towards its imposition, to try and understand the nuances that this extraordinary power has carried in Indian jurisprudence.